Vehicle's Interior Movement Detection and Notification System - Ikhwan Hafiz, Muhamad; Fairuz Rizal, Mohamad Rashidi (2013)
Nowadays, there are lots of incident happening in a parked vehicle itself rather than on the road accidents. From leaving a child locked alone in a vehicle to robbers hiding in the back-seat are some of the cases that involve incidents occurred in a non-moving vehicle. Even though the vehicleâs alarm system has been activated, but the main purpose of the alarm is to keep the car safe from outside intrusion, not inside. The proposed system will detect any motion or movement from the vehicleâs interior and informed the owner by sending an SMS alert message. The system has been successfully designed and tested with low-cost material to encourage its instalment on almost any type of vehicle.